Superheroes Can't Save You : Epic Examples of Historic Heresies - Miles, Todd L. (B & H Academic, 2018)
"Comic superheroes embody the hopes of a world that is desperate for a savior. But those comic creations cannot save us from our greatest foes--sin and death. Throughout the history of the Church there have been bad ideas, misconceptions, and heretical presentations of Jesus. Each one of these heresies fails to present Jesus as the Bible reveals him. In Superheroes Can't Save You, Todd Miles demonstrates how these ancient heresies are embodied in contemporary comic superheroes. Miles compares something everybody already knows (who the superheroes are) with what they need to know (who Jesus is), in a book that makes vitally important Christian truths understandable and applicable to a wide audience."--